2014
DOI: 10.1007/s12639-014-0499-2
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Tc Ia discrete type unit Trypanosoma cruzi in Yucatan Mexico

Abstract: The etiologic agent Trypanosoma cruzi (Tc) has been grouped into six discrete type units (DTU I-VI); within DTU-I exists four subgroups defined Ia-Id. In Colombia, the genotype Ia is associated with human infection and domiciliated Rhodnius vector. In the Yucatan Peninsula of Mexico, the main vector involved in T. cruzi transmission is Triatoma dimidiata predominantly via sylvatic and peridomiciliated cycles. In this study, multiple sequence analysis of mini-exon intergenic regions of T. cruzi isolates obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…cruzi genotyping, DTUs reported for T . dimidiata are TcI (TcIa, TcId), TcII, TcV and TcVI [ 7 , 9 , 15 17 ]. This species feeds on many hosts, including sylvatic, domestic species, and humans [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…cruzi genotyping, DTUs reported for T . dimidiata are TcI (TcIa, TcId), TcII, TcV and TcVI [ 7 , 9 , 15 17 ]. This species feeds on many hosts, including sylvatic, domestic species, and humans [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different infection rates with T. cruzi have been reported in Mexico, Guatemala, Ecuador, Costa Rica, Belize, and Colombia, ranging between 13.7-60% [5][6][7][8][9][10][11][12][13][14]. Regarding T. cruzi genotyping, DTUs reported for T. dimidiata are TcI (TcIa, TcId), TcII, TcV and TcVI [7,9,[15][16][17]. This species feeds on many hosts, including sylvatic, domestic species, and humans [17].…”
Section: Introductionmentioning
confidence: 99%
“…The TcI genotype is widely distributed in northern South America, Central America and Mexico, and is responsible for the majority of the clinical manifestations of Chagas disease in Mexican patients (Monteon et al ., 2016). Mexican strains of T. cruzi I (TcIa) have distinct biological characteristics such as metacyclogenesis, growth, infectivity and they also differ in their ability to invade cells and cause infection (Gómez-Hernández et al ., 2011, 2019; Barbosa et al ., 2019 a , 2019 b ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that historical studies [ 21 , 22 , 26 ], and the findings of the present work, confirmed that TcI is the only genotype detected in Mexico from human isolates from various states of the Mexican Republic, and that there is no genetic variability in any of them, it is possible to propose the development of in silico strategies for the production of antigens to optimise the diagnosis of Chagas disease such as quantitative ELISA methods that use this region of Tc24 without the need for parasitic cultures, and with the possibility of reducing biosafety requirements in diagnostic laboratories. For this reason, the invariance of the Tc24 fragment present in the only DTU (TcI) isolated from human patients in Mexico may offer hope for the production of better diagnostic systems and the potential development of a vaccine.…”
Section: Discussionmentioning
confidence: 99%